The Effect of Parenting Style and Self-Regulation on Smartphone Addiction Through Students’ Anxiety - Atikah, Tera Pertiwi; Sugiyo, Sugiyo; Awalya, Awalya (Universitas Negeri Semarang, 2023)
Vocational high school students are vulnerable to getting addicted to smartphones at a high rate. Therefore, the present study examined the effect of parental styles and self-regulation on smartphone addiction through anxiety. It was correlational research which used an expo facto design with the samples of 329 students. In collecting the data, the instruments of Smartphone Addiction Scale (SAS), Hamilton Anxiety Rating Scale (HARS), EMBU (Swedish acronym for Egna Minnen Beträffande Uppfostran [My memories of upbringing], and the Short Self-Regulation Questionnaire (SSRQ) were used following the results of validity and reliability tests. Once the students’ data was collected, the multiple regression analysis with two sub-structural models was carried out. It showed that parenting styles and self-regulation had a partial effect on anxiety, and anxiety influenced smartphone addiction. In addition, anxiety mediated the effect of parenting styles on smartphone addiction and the effect of self-regulation on smartphone addiction.